2009
DOI: 10.2807/ese.14.17.19190-en
|View full text |Cite
|
Sign up to set email alerts
|

National Hand Hygiene Campaigns in Europe, 2000-2009

Abstract: Hand hygiene represents the single most effective way to prevent healthcare-associated infections. The World Health Organization, as part of its First Global Patient Safety Challenge, recommends implementation of multi-faceted strategies to increase compliance with hand hygiene. A questionnaire was sent by the European Centre for Disease Prevention and Control to 30 European countries, regarding the availability and organisation of their national hand hygiene campaigns. All countries responded. Thirteen countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The level of awareness to hygiene practices among study participants was highly variable, with a range of good scores ranging from 9.5 percent to 32.5 percent. This finding is consistent with the findings of a recent study [12], which found that in the absence of specific interventions, the rate of compliance by HCWs was 38.7 percent. Hand washing with soap and water or antiseptic soap is recommended.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The level of awareness to hygiene practices among study participants was highly variable, with a range of good scores ranging from 9.5 percent to 32.5 percent. This finding is consistent with the findings of a recent study [12], which found that in the absence of specific interventions, the rate of compliance by HCWs was 38.7 percent. Hand washing with soap and water or antiseptic soap is recommended.…”
Section: Discussionsupporting
confidence: 93%
“…A major change in these guidelines was the recommendation to use alcohol-based hand rubs for non-soiling hand decontamination between patient contacts and liquid soap and water for visibly soiled hands. As part of its global alliance for patient safety, it introduced the first Global Patient Safety Challenge in 2005 [12,13]. In 2006, draught guidelines on "Hand Hygiene in Health Care" were published and tested [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…World Health Organization (WHO) in 2005 launched worldwide hand hygiene campaign based on the slogan "clean care is safe care" which is geared towards patient safety (Magiorakos et al, 2009 The most known method microorganisms are conveyed from an individual to another person or object is through hands (WHO, 2009). People contaminate their hands through coughing or sneezing in which they touch surfaces or touch each other without cleansing hands thus transmit pathogens.…”
Section: Hand Hygiene In Healthcare Among Health Care Workersmentioning
confidence: 99%
“…Good infection control practices, including hand hygiene as well as the screening and isolation of infected patients are necessary to prevent the spread of resistant bacteria. Several European countries have or have had national or regional campaigns on hand hygiene [2], but improving hand hygiene practices remains a challenge in many countries. A European Union (EU) Council Recommendation on patient safety, including the prevention and control of healthcare-associated infections has been adopted by EU Health Ministers on 9 June 2009 and lists a series of actions in this area [3].…”
mentioning
confidence: 99%